Lack of Nuclear Localization of the Creb3l1 Transcription Factor Causes Defects in Caudal Fin Bifurcation in Zebrafish Danio rerio - VanWinkle, Peyton E. (2024)
Introduction: The formation of normal bone and bone healing requires the cAMP-responsive element binding protein 3-like-1 (Creb3l1) transmembrane transcription factor, as deletion of the murine CREB3L1 results in osteopenic animals with limited capacity to repair bone after a fracture. Creb3l1 undergoes regulated intramembrane proteolysis (RIP) to release the N-terminal transcription activating (TA) fragment that enters the nucleus and regulates the expression of target genes. Methods: To expand our understanding of Creb3l1’s role in skeletal development and skeletal patterning, we aimed to generate animals expressing only the TA fragment of Creb3l1 lacking the transmembrane domain and thereby not regulated through RIP. However, the CRISPR/Cas9-mediated genome editing in zebrafish Danio rerio caused a frameshift mutation that added 56 random amino acids at the C-terminus of the TA fragment (TA+), making it unable to enter the nucleus. Thus, TA+ does not regulate transcription, and the creb3l1TA+/TA+ fish do not mediate creb3l1-dependent transcription. Results: We document that the creb3l1TA+/TA+ fish exhibit defects in the patterning of caudal fin lepidotrichia, with significantly distalized points of proximal bifurcation and decreased secondary bifurcations. Moreover, using the caudal fin amputation model, we show that creb3l1TA+/TA+ fish have decreased regeneration and that their regenerates replicate the distalization and bifurcation defects observed in intact fins of creb3l1TA+/TA+ animals. These defects correlate with altered expression of the shha and ptch2 components of the Sonic Hedgehog signaling pathway in creb3l1TA+/TA+ regenerates. Conclusion: Together, our results uncover a previously unknown intersection between Creb3l1 and the Sonic Hedgehog pathway and document a novel role of Creb3l1 in tissue patterning.